Comparative Performance Effectiveness of the Portable Food Balls Extrusion Machine - Bonito, Ana Maria A. (JPAIR Multidisciplinary Research, 2013)
This study developed a portable extrusion machine for food balls products. The study used the Research and Development (R&D) process for it involved the preparation and construction of a finished product that can be used in the field of education. The extrusion machine’s cost efficiency was 10 times better than the manual method but twice lower compared to the commercial machine. There was significant variation in the weights of the food balls produced by the three methods, and the instructional and commercial value of the machine obtained an overall mean rating of 4.46 or very satisfactory. Thus, it is technically feasible to construct the portable extrusion machine in view of the expected functionality of the designed parts, the availability of supplies and materials and affordability of its cost. The construction of the machine requires procedure to follow for ease and accuracy. The portable extrusion machine is superior over the manual method but inferior to commercial units as to production ratio. Furthermore, it is more economically viable to use the portable extrusion machine for small-scale food balls production than the manual method. Potential for technology transfer/ generation and business incubation should be conducted before its release in the Philippine market.
Keywords: Food Science Technology; portable extrusion machine; research and development; Philippines